2015
DOI: 10.1155/2015/204628
|View full text |Cite
|
Sign up to set email alerts
|

Altered Spontaneous Brain Activity in Schizophrenia: A Meta-Analysis and a Large-Sample Study

Abstract: Altered spontaneous brain activity as measured by ALFF, fALFF, and ReHo has been reported in schizophrenia, but no consensus has been reached on alternations of these indexes in the disorder. We aimed to clarify the regional alterations in ALFF, fALFF, and ReHo in schizophrenia using a meta-analysis and a large-sample validation. A meta-analysis of activation likelihood estimation was conducted based on the abnormal foci of ten studies. A large sample of 86 schizophrenia patients and 89 healthy controls was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
70
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 77 publications
15
70
0
Order By: Relevance
“…However, only overexpression of HDAC1 in the mPFC, but not in the dorsal (14) or ventral hippocampus (this study), causes schizophrenia-like phenotypes. This finding indicates that HDAC1 in the mPFC, a brain region intimately linked to schizophrenia (43,44), may control different molecular pathways compared with other brain regions, such as the hippocampus. In line with this observation, the concentration of systemically injected MS-275 leading to increased bulk levels of histone 3 acetylation in the prefrontal cortex of mice is fourfold lower compared with the dose needed to observe the same effect in hippocampal tissue (45).…”
Section: Discussionmentioning
confidence: 97%
“…However, only overexpression of HDAC1 in the mPFC, but not in the dorsal (14) or ventral hippocampus (this study), causes schizophrenia-like phenotypes. This finding indicates that HDAC1 in the mPFC, a brain region intimately linked to schizophrenia (43,44), may control different molecular pathways compared with other brain regions, such as the hippocampus. In line with this observation, the concentration of systemically injected MS-275 leading to increased bulk levels of histone 3 acetylation in the prefrontal cortex of mice is fourfold lower compared with the dose needed to observe the same effect in hippocampal tissue (45).…”
Section: Discussionmentioning
confidence: 97%
“…To achieve better comparability between studies in animals and humans, we investigated fALFF in task-free resting states. fALFF has been applied as a proxy measure of spontaneous neural activity strength and has been used increasingly as a biomarker of neuropsychiatric diseases, including Alzheimer's disease (Zhou et al, 2015), schizophrenia (Xu et al, 2015), and depression (Liu et al, 2016). Several studies reported significant correlations of fALFF values and symptom severity in patients (Chen et al, 2015;Fryer et al, 2015) as well as behavioral performance in healthy humans (van Dam et al, 2015), suggesting a close association between resting-state fALFFs and specific behavioral parameters.…”
Section: Discussionmentioning
confidence: 99%
“…For this particular reason, we used fractional amplitude of low-frequency fluctuations (fALFF), because fALFF captures the relative magnitude of blood oxygen level-dependent (BOLD) signal changes on INA and might help to identify brain regions/networks with aberrant local functioning (Egorova, Veldsman, Cumming, & Brodtmann, 2017;Kubera et al, 2019). Whereas ReHo measures connectivity between a given voxel and its neighbors in the time domain (Long et al, 2008;Zang et al, 2004), ALFF measures signal variability of a single voxel in the frequency domain (Xu, Zhuo, Qin, Zhu, & Yu, 2015). Furthermore, fALFF is designed to reduce the sensitivity to physiological noise.…”
Section: Introductionmentioning
confidence: 99%
“…Still, one of the major benefits of using fALFF and combining both modalities is getting the information about both GMV and INA as well as increasing the power of data fusion analysis. There are also several recent fMRI studies that have successfully used fusion ICA methods with fALFF in healthy and SSD samples Hirjak, Rashidi, et al, 2019;Kubera et al, 2019;Lottman et al, 2018;Xu et al, 2015). Finally, GMV volume changes can cause spatiotemporal changes in INA and these joint network alterations might result in aberrant sensorimotor functioning and the development of NSS in SSD patients (Mittal, Bernard, & Northoff, 2017;Northoff & Duncan, 2016).…”
Section: Introductionmentioning
confidence: 99%